UPAYA BIMBINGAN DAN PENYULUHAN BHABINKAMTIMAS DALAM PENCEGAHAN TINDAK PIDANA KEKERASAN SEKSUAL ANAK DIWILAYAH HUKUM POLRES WONOSOBO - Ahmad Rizky Siregar (Advances in Police Science Research Journal, 2022)
Social phenomena resulting from the transformation of the birth of an integrated society and culture universally by influencing changes in people's behavior through technological information that is easily accessible. The background of this study arises due to an increase in cases of sexual violence. The purpose of this study is to describe the implementation and efforts of Bhabinkamtibmas guidance and counseling in the prevention of child sexual violence. Theories used Management Theory (Drs. H Malayu S.P Hasibuan) and Cooperation Theory (Thomson and Perry). The concept of this research is the concept of prevention and the concept of Bhabinkamtibmas. This research was conducted on Bhabinkamtibmas Wonosobo Police using a qualitative approach. Data sources are obtained through interviews with sources in research objects. Data is analyzed directly and after data collection through the stages of collection, data reduction, data presentation and conclusion drawing. From the results of discussions based on existing conceptual literature and interviews in the can be that the implementation of guidance and counseling has not been maximized in a prevention of Criminal Acts, especially the Criminal Act of Child Sexual Violence carried out by Bhabinkamtibmas Wonosobo Police. The conclusions in this study show that the implementation and guidance and counseling efforts carried out by Bhabinkamtibas Wonosobo Police still require evaluation by the supervisory parties of guidance and counseling activities and cooperation between internal and external parties in the implementation of Guidance and counseling. Advice from the author related to the results of the study to strive to improve the quality and quantity of Bhabinkamtibmas Wonosobo Police through education and training.